ANALYSIS OF KARST ROCK DESERTIFICATION IN THE TROPICAL KARST REGION OF GUNUNG SEWU, TEPUS, GUNUNGKIDUL - Fathi Muzaqi; Pipit Wijayanti (Universitas Sebelas Maret (UNS), 2025)
This study investigates the spatial dynamics of Karst Rock Desertification in the tropical karst region of Tepus District, Gunungkidul Regency, using Sentinel-2A imagery and remote sensing indices including NDVI, NDRI, FVC, and Fr. Although various studies have examined KRD in different karst regions using NDVI or NDRI individually, few have integrated multiple indices to capture both vegetation degradation and rock exposure simultaneously. Moreover, most previous studies rely on medium-resolution imagery like Landsat, which limits spatial detail, and rarely focus on the tropical karst of Indonesia. KRD, characterized by soil degradation and vegetation loss in karst landscapes, poses significant ecological threats due to its rapid and often irreversible impacts. The research employed a quantitative descriptive method combined with spatial-temporal analysis using Google Earth Engine and ArcGIS to assess land cover changes between 2019 and 2024. The analysis focused on identifying rock desertification by utilizing NDVI with FVC and the NDRI with FR. Field observations validated these findings, showing clear distinctions in soil depth and vegetation between degradation levels. The results showed significant changes in vegetation cover and rock exposure between 2019 and 2024. The Non-Rocky Desertification area decreased from 25.65% to 9.39%, while the Potential Rocky Desertification zone increased from 73.75% to 90.12%. In terms of vegetation, the “Nothing” category rose from 6.42% to 2.51%, while Moderate vegetation cover declined from 23.20% to 23.51%, and Extremely Severe decreased from 9.68% to 19.11%. These findings indicate that approximately 40% of the study area is now affected by moderate to severe desertification, emphasizing the urgent need for conservation and sustainable land management. The study highlights the critical role of vegetation management and sustainable land use to curb the advancement of desertification. These findings contribute to understanding karst ecosystem vulnerability and inform future ecological restoration strategies.